Individual Employment Contracts. - Malcomson, J (School of Social Sciences (University of Southampton), 1998)
This chapter reviews recent developments in the study of individual employment contracts. It discusses three reasons for an employer and an employee to have a contract: (i) to allocate risk in a way different from a spot market; (2) to enhance the efficiency of investment decisions by protecting the return on investments made by one party from being captured by the other; and (3) to motivate the employee by making compensation depend on performance. The main emphasis is on issues that arise from the problems of enforcing contracts in practice and from renegotiation by mutual agreement.